Optimization of process variables of continuous type ohmic heating for milk pasteurization - Amitabh, Anupam; Jain, Sanjay Kumar; KUMAR, VISHAL (Indian Journal of Dairy Science, 2019)
Experiments were conducted according to Box Behnken Design for optimization of ohmic heating (OH) for pasteurization of milk (fat content: 3 per cent, 4.5 per cent, and 6 per cent) in a continuous type ohmic heating unit. The three OH process variables were fat content of milk, applied voltage and inlet temperature of milk. Optimum conditions obtained by numerical optimization were fat content of 5per cent, applied voltage 30 V and feeding temperature of 40 oC in order to obtain optimized yield as final temperature (T) – 72 oC; and specific performance coefficient (SPC) - 79.89 with desirability of 0.753.